Multidisciplinary Management of Acute and Chronic Pancreatitis - Massani, Marco; Stecca, Tommaso (IntechOpen, 2023)
Pancreatitis is a common disease of the digestive system with a high mortality and complication rate. The successful management of patients requires a multidisciplinary team of gastroenterologists, surgeons, interventional radiologists, and specialists in critical care medicine and nutrition. The odyssey in managing pancreatitis is a notable example of how evidence-based knowledge leads to improvement in patient care. In the last decades, operative treatment has moved towards minimally invasive techniques such as laparoscopy and endoscopic or percutaneous retroperitoneal approaches. New insights into nutritional and anesthesiology management have further improved the treatment and outcomes of pancreatitis. This book provides a comprehensive overview of this condition with chapters on physiology and pathophysiology, surgical and endoscopic management, enteral and parenteral nutritional interventions, and much more.